Pengaruh Kepemimpinan, Kompetensi, Teknologi Informasi Terhadap Akuntabilitas Pengelola Dana Desa di Kecamatan Rakit Kulim, Riau - Evi Marlina; Sri Rahmayanti; Ameilia Dwi Rur Afdilah Futri (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2021)
This study examines the influence of leadership, competence and information technology on the accountability of village fund management in Rakit Kulim sub-district, Indragiri Hulu, Riau. Regarding the objectives of this study, three hypotheses were formulated, namely leadership, competence and information technology on the accountability of village fund management. This study uses a quantitative approach. Data collection was carried out using a questionnaire, from 76 questionnaires distributed to the village government apparatus of the Rakit Kulim sub-district and all of them returned. To test the hypothesis, regression analysis was carried out using SPSS version 17.00. Before testing the hypothesis, testing the validity, reliability and classic regression assumptions is carried out. This study shows that leadership, competence and information technology have a significant effect on the accountability of village fund management.